Prevention of Nosocomial Infections in Neonatal Intensive Care Units - Manzoni, Paolo; De Luca, Daniele; Stronati, Mauro; Jacqz-Aigrain, Evelyne; Ruffinazzi, Giulia; Luparia, Martina; Tavella, Elena; Boano, Elena; Castagnola, Elio; Mostert, Michael; Farina, Daniele (American Journal of Perinatology, 2013)
Neonatal sepsis causes a huge burden of morbidity and mortality and includes bloodstream, urine, cerebrospinal, peritoneal, and lung infections as well as infections starting from burns and wounds, or from any other usually sterile sites. It is associated with cytokine - and biomediator-induced disorders of respiratory, hemodynamic, and metabolic processes. Neonates in the neonatal intensive care unit feature many specific risk factors for bacterial and fungal sepsis. Loss of gut commensals such as Bifidobacteria and Lactobacilli spp., as occurs with prolonged antibiotic treatments, delayed enteral feeding, or nursing in incubators, translates into proliferation of pathogenic microflora and abnormal gut colonization. Prompt diagnosis and effective treatment do not protect septic neonates form the risk of late neurodevelopmental impairment in the survivors. Thus prevention of bacterial and fungal infection is crucial in these settings of unique patients. In this view, improving neonatal management is a key step, and this includes promotion of breast-feeding and hygiene measures, adoption of a cautious central venous catheter policy, enhancement of the enteric microbiota composition with the supplementation of probiotics, and medical stewardship concerning H2 blockers with restriction of their use. Additional measures may include the use of lactoferrin, fluconazole, and nystatin and specific measures to prevent ventilator associated pneumonia.
Keywords: neonate; fluconazole; lactoferrin; sepsis; candida; infection; probiotics